Comprehensive analysis of DNA methylation and prediction of response to neoadjuvanttherapy in locally advanced rectal cancer - Canto, Luisa Matos Do; Barros-Filho, Mateus Camargo; Rainho, Cláudia Aparecida [UNESP]; Marinho, Diogo; Kupper, Bruna Elisa Catin; Begnami, Maria Dirlei Ferreira de Souza; Scapulatempo-Neto, Cristovam; Havelund, Birgitte Mayland; Lindebjerg, Jan; Marchi, Fabio Albuquerque; Baumbach, Jan; Aguiar, Samuel; et al. (MDPI, 2020)
The treatment for locally advanced rectal carcinomas (LARC) is based on neoadjuvant chemoradiotherapy (nCRT) and surgery, which results in pathological complete response (pCR) in up to 30% of patients. Since epigenetic changes may influence response to therapy, we aimed to identify DNA methylation markers predictive of pCR in LARC patients treated with nCRT. We used high-throughput DNA methylation analysis of 32 treatment-naïve LARC biopsies and five normal rectal tissues to explore the predictive value of differentially methylated (DM) CpGs. External validation was carried out with The Cancer Genome Atlas-Rectal Adenocarcinoma (TCGA-READ 99 cases). A classifier based on three-CpGs DM (linked to OBSL1, GPR1, and INSIG1 genes) was able to discriminate pCR from incomplete responders with high sensitivity and specificity. The methylation levels of the selected CpGs confirmed the predictive value of our classifier in 77 LARCs evaluated by bisulfite pyrosequencing. Evaluation of external datasets (TCGA-READ, GSE81006, GSE75546, and GSE39958) reproduced our results. As the three CpGs were mapped near to regulatory elements, we performed an integrative analysis in regions associated with predicted cisregulatory elements. A positive and inverse correlation between DNA methylation and gene expression was found in two CpGs. We propose a novel predictive tool based on three CpGs potentially useful for pretreatment screening of LARC patients and guide the selection of treatment modality.
Keywords: 5-fluorouracil; High-throughput DNA methylation analysis; Predictive biomarker; Translational research